Patty's industrial hygiene - Cohrssen, Barbara; Rose, Vernon E. (John Wiley, 2010)
An updated edition of the cornerstone reference work for chemists, engineers, toxicologists, and occupational safety personnel, the new Sixth Edition of Patty's Industrial Hygiene offers timely coverage on natural disasters, exposures to biological agents, and potential acts of terrorism